2018
DOI: 10.1093/jac/dky154
|View full text |Cite
|
Sign up to set email alerts
|

High discordance in blood and genital tract HIV-1 drug resistance in Indian women failing first-line therapy

Abstract: We identified high resistance and high inter-compartmental resistance discordance in Indian women, which might lead to unrecognized resistance transmission and re-emergence compromising treatment outcomes, particularly relevant to countries like India, where sexual HIV transmission is predominant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…A few reports found HIV drug resistance profiles in CVL and blood that were discordant [68][69][70]. Recent cases are included in Table 2 [71,72]. A study of women with virologic failure found complete concordance between blood plasma, blood cells, and genital tract in only 2 of 20 women with 14 having drug resistance mutations detected in genital tract but not in blood plasma [71].…”
Section: Genital Tract Compartmentalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A few reports found HIV drug resistance profiles in CVL and blood that were discordant [68][69][70]. Recent cases are included in Table 2 [71,72]. A study of women with virologic failure found complete concordance between blood plasma, blood cells, and genital tract in only 2 of 20 women with 14 having drug resistance mutations detected in genital tract but not in blood plasma [71].…”
Section: Genital Tract Compartmentalizationmentioning
confidence: 99%
“…Recent cases are included in Table 2 [71,72]. A study of women with virologic failure found complete concordance between blood plasma, blood cells, and genital tract in only 2 of 20 women with 14 having drug resistance mutations detected in genital tract but not in blood plasma [71]. It is, however, not known if these mutations would persist or would have impacted the treatment response.…”
Section: Genital Tract Compartmentalizationmentioning
confidence: 99%